2012
DOI: 10.1177/039463201202500404
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Analogue Stimulates Keratinocyte Proliferation but Inhibits Cell Differentiation in Epidermis

Abstract: Gross clinical manifestations of thyroid hormone (TH) imbalance are often first seen in the skin where TH plays an integral role in sustaining natural function. Although mounting evidence suggests . that TH plays an. important role in epidermal proliferation and wound healing, the physiologic role of thyroid hormone in skin is not well lulderstood. In the current study, we investigated the effect of a natural thyroid hormone analogue -3, 3', 5-triiodo~thyroaceticacid (TRIAC) on regulating proliferation and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
(47 reference statements)
0
10
1
Order By: Relevance
“…Topical application of TA 3 increases dermal thickness and prevents glucocorticoid-induced skin atrophy in mice and humans (Faergemann et al 2002, Yazdanparast et al 2006a, and stimulates procollagen synthesis and keratinocyte proliferation in human skin (Yazdanparast et al 2004, Zhang et al 2012, but has no beneficial effects on plaque psoriasis (Vahlquist et al 2004). …”
Section: Skinmentioning
confidence: 99%
“…Topical application of TA 3 increases dermal thickness and prevents glucocorticoid-induced skin atrophy in mice and humans (Faergemann et al 2002, Yazdanparast et al 2006a, and stimulates procollagen synthesis and keratinocyte proliferation in human skin (Yazdanparast et al 2004, Zhang et al 2012, but has no beneficial effects on plaque psoriasis (Vahlquist et al 2004). …”
Section: Skinmentioning
confidence: 99%
“…We observed that the levels of cyclins D1 and D3 were increased in the tumors grown in the hyperthyroid animals. Increased cyclin D1, which regulates the entry into the G1 phase of the cell cycle, has been widely linked to the regulation of the cell cycle by THs in various cell types (Ledda-Columbano et al 2006, Verga Falzacappa et al 2012, Zhang et al 2012. Many lines of evidence have indicated that cyclins D1 and D3 are involved in T-cell lymphomagenesis and are important molecular markers of oncogenic potential in T cell lymphomas (Teramoto et al 1999, Cheng et al 2008.…”
Section: Figurementioning
confidence: 99%
“…In addition, the treatment of rat cardiomyocytes with T3 increases the expression levels of cyclin D1 and thus induces the cell cycle progression [45]. In accordance with these results, the increment of Cyclin D1 has been widely linked to the TH-mediated regulation of the cell cycle in various cell types [46][47].…”
Section: Direct Action Of Ths On Tcl Cells Involves Both Genomic and mentioning
confidence: 53%